Textile dyes as a major problem for the environment: Comparative removal of the highly toxic textile dyes from aqueous solution - Aseel M Aljeboree (Caspian Journal of Environmental Sciences, 2021)
Environmental pollution is one of the most important and main problems that the world is facing today. Global production and use of chemical compounds, many of which are resistant to biodegradation, have increased significantly in recent decades. These compounds enter the environment after consumption, and therefore, it is necessary to provide solutions to reduce consumption and remove pollutants from the environment. Removing the textile dyes of crystal violet (CV) and methylene blue (MB) from aqueous solution by CNT/TiO2 surface was studied. We considered several physio-chemical parameters for example, contact time, primary concentration dye (5-50 mg L-1), adsorbent amount (0.01-0.1 gm), as well as temperature (15, 35, and 50 °C) in technique batch-adsorption. The output appeared absorbing two favorable dyes MB, CV at the basic pH. Moreover, removal present elevated by the increased amount of adsorbent, while decreased by uprising the primary concentration of dye, and agitation time bath of the two dyes. The adsorption capacity (Qe) upraised by the increased contact time and initial concentration of dyes, and then declined by the adsorbent weight and the procedure of temperature. The equilibrium data were estimated utilizing Freundlich and Langmuir isotherms. The Freundlich isotherm describes the best uptake of MB and CV dyes. The adsorption of CV and MB in the present study on the CNT/TiO2 was heterogeneous with multi-layers. The results have shown immense potential, and it was found that the correlation coefficient value deals with the dyes, while the Langmuir equation did not exhibit good correlation of dyes.